The effect of soft and extreme action in public complaint behavior on satisfaction with complaint handling - A. Rahman, Mohd Khirzanbadzli; Haron, Sharifah Azizah; Paim, Laily; Osman, Syuhaily; Yunus, Noorlaila; Wee, Hassnah (Econjournals, 2016)
Malaysia is experiencing a tremendous increase in mobile phone services users. Service providers are providing various complaint channels as one of the ways to improve services. Although complaining provides significant impact to organizations as well as to complainers or consumers, ironically the number of public complaints is insignificant. Based on previous study, two actions in public complaint namely public complaint soft action and public complaint extreme action were used in this study as the exogenous variables and satisfaction with complaint handling (SATCOM) as the endogenous variable. A total of 285 complainers of mobile phone user were selected as respondents. The values for goodness-of-fit, average variance extracted, construct reliability and convergent validity confirmed the measurement model prior proceeding to structural model. The structural model revealed mixed results that provide indication of consumer SATCOM specifically in the mobile phone service industry.